Wilson disease in Costa Rica: Pediatric phenotype and genotype characterization - Penon‐Portmann, Monica (JIMD Rep, 2020)
INTRODUCTION: The prevalence of Wilson disease (WD) in Costa Rica is among the highest reported in the world, 4.9:100 000. Previous investigators have also described a burden of autosomal recessive conditions in this country. Genetic testing for WD began in 2010 as a strategy for earlier detection due to the country's high prevalence. Here we describe what we have learned about the genotype and phenotype of the Costa Rican pediatric population with WD. METHODS: We completed a retrospective review of medical records from pediatric individuals (<18 years of age) with molecular testing for ATP7B between 2010 and 2015. We documented phenotype and genotype for cases with WD as defined by the international scoring system. RESULTS: Thirty‐four WD cases from 28 families were included, 15 female and 19 male patients. The most frequent pathogenic variant in ATP7B was NM_000053:c.3809A>G, p.Asn1270Ser, with 58.8% of affected individuals homozygous for this variant. Age of diagnosis ranged from 1 to 17 years, with an average of 8.8 ± 3.6 years. All individuals who presented with acute liver failure (n = 6) were homozygous for the p.Asn1270Ser variant (Chi‐squared, P < .05). DISCUSSION: Molecular testing has facilitated the detection of presymptomatic patients with WD in Costa Rica. We hope that ongoing efforts in the delivery of clinical services lead to optimized molecular screening for WD and other genetic conditions in Costa Rica.